Squamosamide Derivative FLZ Diminishes Aberrant Mitochondrial Fission by Inhibiting Dynamin-Related Protein 1 - Yang, Hanyu; Wang, Lu; Zang, Caixia; Yang, Xu; Bao, Xiuqi; Shang, Junmei; Zhang, Zihong; Liu, Hui; Ju, Cheng; Li, Fangyuan; Yuan, Fangyu; Zhang, Dan (Frontiers in Pharmacology, 2021)
Mitochondrial dysfunction is involved in the pathogenesis of Parkinson’s disease (PD). Mitochondrial morphology is dynamic and precisely regulated by mitochondrial fission and fusion machinery. Aberrant mitochondrial fragmentation, which can result in cell death, is controlled by the mitochondrial fission protein, dynamin-related protein 1 (Drp1). Our previous results demonstrated that FLZ could correct mitochondrial dysfunction, but the effect of FLZ on mitochondrial dynamics remain uncharacterized. In this study, we investigated the effect of FLZ and the role of Drp1 on 1-methyl-4-phenylpyridinium (MPP+)–induced mitochondrial fission in neurons. We observed that FLZ blocked Drp1, inhibited Drp1 enzyme activity, and reduced excessive mitochondrial fission in cultured neurons. Furthermore, by inhibiting mitochondrial fission and ROS production, FLZ improved mitochondrial integrity and membrane potential, resulting in neuroprotection. FLZ curtailed the reduction of synaptic branches of primary cultured dopaminergic neurons caused by MPP+ exposure, reduced abnormal fission, restored normal mitochondrial distribution in neurons, and exhibited protective effects on dopaminergic neurons. The in vitro research results were validated using an MPTP-induced PD mouse model. The in vivo results revealed that FLZ significantly reduced the mitochondrial translocation of Drp1 in the midbrain of PD mice, which, in turn, reduced the mitochondrial fragmentation in mouse substantia nigra neurons. FLZ also protected dopaminergic neurons in PD mice and increased the dopamine content in the striatum, which improved the motor coordination ability of the mice. These findings elucidate this newly discovered mechanism through which FLZ produces neuroprotection in PD.